Biomechanical analysis of the 2017 European indoor champion in the women`s long jump: case report - Panoutsakopoulos, V.; Theodorou, A. S.; Kotzamanidou, M. C.; Kollias, I. A. (Journal of Exercise and Quality of Life, 2020)
The purpose of the present study was to present a report of the biomechanical analysis of the winner of the Women`s Long Jump in the 2017 European Indoor Championships held in Belgrade, Serbia. All attempts of the examined jumper (age: 26.8 years; height: 1.76 m; mass: 65 kg), who won the competition with an official distance of 7.24 m, were recorded with a high-speed video camera operating at a sampling frequency of 300 fps. The kinematical parameters of the final steps of the approach and the take-off were calculated using with a panning analysis method. Results revealed that the best jump was accomplished with the highest individual value for vertical take-off velocity (2.94 m/s). The less variable parameter of the approach was the horizontal velocity (9.6±0.1 m/s), while the most variable parameter was the contact/flight time ratio for the last step (0.65±0.09). An inter-limb difference was observed for step frequency in the final steps. For the best jump, the examined athlete had an exact coincidence at the final step of the adjustment needed and the adjustment made in order to optimize the foot placement on the board. The examined jumper`s biomechanical parameters were in accordance with reports about her technique analyzed in major international competitions. The findings of the present report are in agreement with previous research concerning the importance of vertical take-off velocity, the accuracy of foot placement on the board and the observed reliance and asymmetries in the step parameters of the final approach.